Egyptian HCPs' awareness, attitudes and practice to SHS exposure among pregnant women and children. (20th October 2021) - Hassanein, Z; Langley, T; Murray, R; Bogdanovica, I; Leonardi-Bee, J
Abstract: Background and aims: Around half of Egyptian pregnant non-smoking women and children are exposed to secondhand smoke (SHS), which cause serious morbidities. Health care professionals (HCPs) are well placed to help reduce SHS exposure by encouraging avoiding SHS. This study aimed to explore risk-awareness, attitudes and practice of HCPs in relation to SHS exposure among pregnant women and children in Egypt. Methods: Cross-sectional survey of HCPs working in public maternal and child health clinics in Assiut city, Egypt. The survey included questions on risk-awareness, attitudes and counselling practice. Descriptive and regression analysis was performed to explore factors associated with high risk-awareness, supportive attitudes, and good counselling practice. Results: 367 HCPs participated in the survey with the majority being nurses (45%) and gynaecologists/obstetricians (21%). 12.5% of HCPs were smokers, and considerable proportion of HCPs reported being exposed to SHS at workplace (70.3%) and at home (51.7%). Just over half of all HCPs (55.9%) had high SHS risk awareness. Speciality, serving urban communities, and home SHS exposure were significantly associated with high-risk awareness. 52.9% of HCPs had supportive attitude towards preventing SHS exposure. Being female, serving rural communities, home SHS exposure were significantly associated with supportive attitudes. Only 51.8% of HCPs reported good counselling practice, which was explaining SHS hazards and advising to avoid it. Being female, serving rural communities, not exposed to SHS at home, and previous training on smoking cessation service were significantly associated with good counselling practice. Conclusions: HCPs' awareness, attitudes and practice regarding the risks of SHS to pregnant women and children in Egypt are at low levels. Training is required for HCPs to improve their knowledge and skills and be able to help pregnant women and children to avoid SHS exposure and reduce consequent health burden. Key messages: HCPs' awareness and practice regarding risks of SHS to pregnant women/children in Egypt are inadequate. HCPs' training is essential to help pregnant women/children to avoid SHS and reduce health burden.